In Situ Performance Evaluation of a Solar Water Heating System for a Hospital Laundry in the Sahel - Flores-Bahamonde, C (Elsevier B.V., 2024)
There is a limited number of empirical studies on the actual energy output of solar water heating systems (SWHSs). In the Sahel, where solar potential is abundant, the transition to sustainable energy solutions requires comprehensive evaluations of SWHSs, including their economic viability. Such assessments are crucial for informed decision-making by stakeholders and for facilitating the widespread adoption of SWHSs, including their integration into industrial processes. This paper presents a year-round experimental study assessing the real-world performance and economic viability of a SWHS integrated into a hospital laundry in Ouagadougou, Burkina Faso. The primary aim of the study is to analyse the practical performance of the integrated collector storage (ICS) SWHS and evaluate its economic viability. The performance of the ICS SWHS is monitored over the course of a year. Data collection included measurements of solar irradiation, ambient temperature, inlet and outlet water temperatures, and energy output of the SWHS. Economic assessments considered factors such as installation costs, energy savings, and payback periods. Environmental implications were evaluated through the estimation of avoided CO2 emissions. The ICS SWHS achieved an efficiency of 38 % and a solar fraction of 17 %, resulting in approximately 1.3 t of avoided CO2 emissions annually. Economic assessments revealed extended payback periods, leading to exploration of alternatives. Subsequently, a water-in-glass evacuated tube collector (ETC) system, deemed more cost-effective, was selected and it indicated superior energy production. Preliminary results suggest compelling payback periods for the ETC system, ranging from 3.1 to 4.5 years under realistic scenarios. The study underscores the significance of practical experimentation, appropriate technology selection, and improved market regulations for informed decision-making. SWHSs present a promising avenue for sustainable energy solutions in the Sahelian region and beyond, offering both economic benefits and environmental impact. © 2024 International Energy Initiative